Book review of: Feichtner, Isabel; Heeg, Susanne; Klingenmeier, Anne; Langlotz, Gesine; Schubel, Katja (Hrsg.) (2025): Stadt – Land – Boden. Verbindende Bodenpolitik zwischen Stadt und Land - Dosch, Fabian (Raumforschung und Raumordnung | Spatial Research and Planning, 2026)
Book review